A catalyst-free and additive-free method for the synthesis of benzothiazolethiones from o-iodoanilines, DMSO and potassium sulfide. Issue 9 (6th April 2018) - Zhu, Xiaoming; Li, Wenguang; Luo, Xiai; Deng, Guobo; Liang, Yun; Liu, Jianbing
Abstract : Under catalyst-free and additive-free conditions, a novel, convenient, environment-friendly method for the synthesis of benzothiazolethiones from o -iodoanilines, K2 S and DMSO has been developed. Abstract : Under catalyst-free and additive-free conditions, a novel, convenient, eco-friendly method for the synthesis of benzothiazolethiones has been developed. The three-component reaction of o -iodoanilines and K2 S with DMSO proceeded smoothly and the corresponding benzothiazolethiones were obtained with good isolated yields. Meanwhile, this method could be used for the synthesis of thioureas from primary diamines. Furthermore, mechanism research showed that DMSO not only functioned as a carbon source, but also as a mild oxidant in this reaction.